AUDIT SISTEM INFORMASI ABSENSI PADA KEJAKSAAN NEGERI KOTA BANDUNG MENGGUNAKAN FRAMEWORK COBIT 5 - Akmal Panji Rabhani; Adela Maharani; Anggia Arfiani Putrie; Devianti Anggraeni; Hadid Fathan Azisabil; Imelda Cantika; Intan Cahyani; Lina Lulus Destianti; Putri Tsania Mahmud; Ricky Firmansyah (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Kejaksaan Negeri Kota Bandung is a unit of the state institutions that carries out state power, particularly in the field of prosecution. Kejaksaan Negeri Kota Bandung implemented an information system to intensify operational activities. Using a computerized tool that is FaceUnlock to record the attendance list of employees. The system must be able to manage, convey, and maintain information security properly. Then, an audit is needed to evaluate the governance of the current information system. In this research, the capability model is used as a measurement of respondent's answers from a questionnaire based on the COBIT 5 framework with the MEA (Monitor, Evaluate, and Assess) domain as a reference. Respondents who were involved in filling out the questionnaire were employees of Kejaksaan Negeri Kota Bandung who carried out SIMPEG operations on daily. Based on the recapitulation of the answers from the respondents, the value of the current capability level is 2.4 in the range 1-4. To get the expected results, there some alternative to intensify SIMPEG's performance at Kejaksaan Negeri Kota Bandung in the future.